2020
DOI: 10.1016/j.ekir.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Postdischarge Health Care Costs and Readmission in Patients With Hyperkalemia-Related Hospitalizations

Abstract: Introduction: Limited evidence is available regarding the postdischarge economic and readmission burdens of hyperkalemia. Methods: Using the IBM MarketScan Commercial and Medicare-Supplemental Claims database (January 1, 2010-December 31, 2014), adult patients with a hospitalization with a hyperkalemia diagnosis (ICD-9-CM 276.7, hyperkalemia cohort) were 1:1 matched with patients with a hospitalization without evidence of hyperkalemia (nonhyperkalemia cohort) on age, chronic kidney disease stage, heart failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…It has been suggested that CKD patients adapt to elevated potassium concentrations through modifications in gastrointestinal secretions which may favor intracellular potassium storage, or by increasing insulinmediated intracellular potassium uptake in splanchnic and peripheral muscle tissues (19). On the other hand, relevant are also the related economic costs that double in the presence of persistent hyperkalemia (20). In a recent retrospective cohort study of 1,499 patients with chronic hyperkalemia and CKD, heart failure or diabetes mellitus followed up for 36 months, the annual healthcare cost per patient with severe hyperkalemia has calculated as double compared to mild hyperkalemia (21).…”
Section: Hyperkalemia In Patients With Ckd Non-dialysismentioning
confidence: 99%
“…It has been suggested that CKD patients adapt to elevated potassium concentrations through modifications in gastrointestinal secretions which may favor intracellular potassium storage, or by increasing insulinmediated intracellular potassium uptake in splanchnic and peripheral muscle tissues (19). On the other hand, relevant are also the related economic costs that double in the presence of persistent hyperkalemia (20). In a recent retrospective cohort study of 1,499 patients with chronic hyperkalemia and CKD, heart failure or diabetes mellitus followed up for 36 months, the annual healthcare cost per patient with severe hyperkalemia has calculated as double compared to mild hyperkalemia (21).…”
Section: Hyperkalemia In Patients With Ckd Non-dialysismentioning
confidence: 99%
“…While there are several published observational studies comparing HRU and healthcare expenditures for patients with and without HK 2,[12][13][14][15] , research regarding the relative effect of different treatment modalities among patients with HK are emerging 14,[19][20][21][22][23][24][25] . Among Medicare Advantage patients with HK in real-world clinical practice, this study aimed to evaluate the outcomes for patients exposed to patiromer compared to patients not exposed to a K + binder.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the United States (US), the prevalence of HK was reported to be 1-2% overall, and potentially as high as 15% among Medicare patients with CKD and/or CHF 11,12 . HK has been reported to be associated with increased healthcare costs and healthcare resource utilization (HRU; eg, inpatient admission and emergency department [ED] encounters) [13][14][15] . In studies using administrative claims data in the US, researchers found that patients with HK incurred 58% higher total healthcare expenditures and were 40% more likely to be readmitted, compared to patients without HK 12,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar data have been shown in 2164 patients at discharge after decompensated heart failure [ 3 ]. Furthermore, the cost of providing care for patients with even moderate HK is double the cost of care for those whose potassium levels are normal [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%